Annual report - National Endowment for the Arts.; National Endowment for the Arts. Public Information Office; National Endowment for the Arts. Office of Public Affairs; National Endowment for the Arts.; National Endowment for the Arts. Office of Communications (Washington, D.C. : Division of Publications, National Endowment for the Arts., 1965)
Reports for <1980>-19 also include the Annual report of the National Council on the Arts.
Report covers fiscal year.
Also available online through the UMass Amherst Open Content Alliance Digitization Project.
Mode of access: Internet.
Vols. for <1980>-198 issued by: Division of Publications, National Endowment for the Arts; 198 -1986 by: Office of Communications, National Endowment for the Arts; 1987-198, 1991- by: National Endowment for the Arts; 198 -1989 by: the Office of Public Affairs, National Endowment for the Arts; 1990 by: Public Information Office, National Endowment for the Arts.
Description based on: 1980.
Report for 1965 is the annual report of the National Council on the Arts; report for 1966 is annual report of the National Endowment for the Arts and the National Council on the Arts. Both are included in electronic holdings.
Keywords: National Endowment for the Arts -- Periodicals; Federal aid to the arts -- United States -- Periodicals